Flood Tidal Risk Modeling on the Coast of West Sulawesi Using Geographic Information Systems to Support Climate Change Adaptation Planning - Haryanto Asri; Hardianti Nur (Politeknik Siber Cerdika Internasional, 2026)
Background: Coastal flooding or tidal inundation (banjir rob) is one of the visible impacts of climate change that increasingly affects coastal regions in Indonesia, including West Sulawesi Province. Sea-level rise, land-use changes, and mangrove degradation have intensified the vulnerability of coastal areas to tidal flooding. Objective: This study aims to model the risk of tidal flooding along the coast of West Sulawesi using Geographic Information Systems (GIS) and to formulate climate change adaptation strategies through spatial and SWOT analyses. Methods: The research utilized spatial datasets, including elevation, slope, distance from the coastline and rivers, land use, and mangrove density. The analysis was conducted using a scoring, weighting, and overlay approach to generate a tidal flood vulnerability map, which was validated using observed flood event data from 2021–2025. Results: The results indicate that low-lying coastal zones below 5 meters above sea level with sparse mangrove cover (particularly in Polewali Mandar, Majene, and Mamuju Regencies) are highly vulnerable to tidal flooding. Spatial projections suggest a significant increase in inundation areas by 2075 in line with projected sea-level rise. Based on the SWOT analysis, the recommended adaptation strategy is an offensive (S–O) approach, emphasizing the utilization of coastal ecosystem potential and conservation policies to promote mangrove-based ecotourism, strengthen community adaptive capacity, and enhance collaboration among government, academia, and local communities. Conclusion: The findings are expected to provide a scientific foundation for climate change mitigation and adaptation planning in the coastal regions of West Sulawesi toward sustainable coastal development.